Synthesis and biological evaluation of salicylic acid analogues of celecoxib as a new class of selective cyclooxygenase-1 inhibitor - Yoon, Sung Hwa; Cho, Duk Yeon; Choi, Seoung Ryoung; Lee, Joo Young; Choi, Dong Kug; Kim, Eunha; Park, Ju Young (Biological and Pharmaceutical Bulletin, 2021)
A series of salicylic acid analogues of celecoxib where the phenylsulfonamide moiety in the structure of celecoxib is replaced by salicylic acid moiety was synthesized and tested for in vitro cyclooxygenase (COX)-1 and COX-2 enzyme inhibition. Among the series, 5-substituted-2-hydroxy-benzoic acid analogues (7a–7h) generally showed better inhibitory activities on both enzymes than 4-substituted-2-hydroxy-ben-zoic acid analogues (12a–12h). In particular, the chloro analogue 7f which had the highest inhibitory effect (IC50=0.0057µM) to COX-1 with excellent COX-1 selectivity (SI=768) can be classified as a new potent and selective COX-1 inhibitor. The high inhibitory potency of 7f was rationalized through the docking simulation of this analogue in the active site of COX-1 enzyme.
Keywords: Catalytic Domain; Celecoxib; Cyclooxygenase 1; Cyclooxygenase Inhibitors; Enzyme Assays; Molecular Docking Simulation; Molecular Structure; Salicylates; Structure-Activity Relationship; Celecoxib salicylic acid analogue; Docking; Selective cyclooxygenase-1 inhibitor